Application of Situational Leadership to the National Voluntary Public Health Accreditation Process - Rabarison, Kristina; Ingram, Richard C.; Holsinger, Jr., James W. (Frontiers in Public Health, 2013)
Successful navigation through the accreditation process developed by the Public Health Accreditation Board (PHAB) requires strong and effective leadership. Situational leadership, a contingency theory of leadership, frequently taught in the public health classroom, has utility for leading a public health agency through this process. As a public health agency pursues accreditation, staff members progress from being uncertain and unfamiliar with the process to being knowledgeable and confident in their ability to fulfill the accreditation requirements. Situational leadership provides a framework that allows leaders to match their leadership styles to the needs of agency personnel. In this paper, the application of situational leadership to accreditation is demonstrated by tracking the process at a progressive Kentucky county public health agency that served as a PHAB beta test site.